2012
DOI: 10.1016/j.socscimed.2012.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change in health care equity using small-area administrative data – Evidence from the English NHS 2001–2008

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent ABSTRACTBackground. This study develops a method for measuring change in socio-economic equity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29] However, these studies do not distinguish emergency and elective treatments.…”
Section: Contextmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] However, these studies do not distinguish emergency and elective treatments.…”
Section: Contextmentioning
confidence: 99%
“…The second paper (Cookson et al., 2012) used an expanded dataset with a vector of population, supply and need variables (including disease prevalence collected as part of the English pay-for-performance scheme, the Quality and Outcomes Framework) in an 8-year panel. It applied a revised methodology to identify change in socio-economic equity of several different categories of health care utilisation over time, including inpatient admissions and outpatient visits.…”
Section: Introductionmentioning
confidence: 99%
“…Cookson et al (2012) found no change in socioeconomic equity of healthcare use between 2001-2002 and 2008-2009 for elective procedures, and some signs that equity might actually have improved slightly, since inpatient admission rates rose slightly faster in lowincome areas than elsewhere. These results raise some optimism that socioeconomic disparities in healthcare utilisation may be impervious to changes in the provider reimbursement system.…”
Section: Equity Of Carementioning
confidence: 85%